Generation of a human induced pluripotent stem cell line UGENTi002-A from an arrhythmogenic cardiomyopathy patient carrying the c.817C>T DSP heterozygous variant and isogenic control using CRISPR/Cas9 editing - Laurens Léger; Jeffrey Aalders; Nina Heymans; Kiara Van Acker-Verberckt; Léa De Bleeckere; Paul Coucke; Björn Menten; Barbara Bauce; Libero Vitiello; Alessandra Rampazzo; Martina Calore; Jolanda van Hengel (Stem Cell Research)
Arrhythmogenic cardiomyopathy is a severe genetic heart muscle disease characterized by fibro-fatty replacement of the myocardium. Pathogenic variants causal for this disease are mainly located in desmosomal genes, including desmoplakin (DSP). Renal epithelial cells were isolated from a patient carrying the heterozygous c.817C>T (p.Q273*, nonsense) pathogenic variant in DSP, and subsequently reprogrammed using the Cytotune®-iPS 2.0 Sendai Reprogramming Kit. An isogenic control line was generated using CRISPR/Cas9 genome editing. The resulting induced pluripotent stem cell lines were characterized and displayed the required traits for in vitro disease modeling.